Effects of music-based voice intervention protocol on vocal amplitude, pitch range, respiratory rate, and quality of life of people with Parkinson’s Disease - Ang, Mei Foong (2019)
Parkinson’s Disease (PD) is a chronic neurodegenerative disease in which the symptoms worsen over time. These symptoms are characterized by motor and non-motor problems marked by tremor at rest, muscular rigidity, and slow movements. In addition, people with Parkinson’s Disease (PwP) are prone to develop voice impairment known as Parkinsonian Dysarthria where latest research suggested 90% of the PwP are affected. Methods: This study explored the effects of Music-based Voice Intervention Protocol (MusVIP) on three vocal parameters including vocal amplitude, respiratory rate, and pitch range, as well as quality of life (QOL) of PwP. 22 PwPs participated in this study and received 120-minutes singing sessions weekly for eight consecutive weeks. One-way repeated measures ANOVA was conducted to compare scores on the three vocal parameters at pre-, co- and post-intervention. QOL was measured through Voice Handicap Index (VHI) and Voice Related Quality of Life (VRQOL) questionnaires at pre- and post-intervention. Pre- and post-intervention interviews were conducted to find out the PwPs’ perceptions on their vocal problems, music and song preferences and feedback on MusVIP. Results: Statistical tests revealed positive significant outcomes on vocal parameters (p ≤ 0.05); paired sample t-test results of the questionnaires reported no significant changes to the QOL, however the mean scores revealed trends of improvements. Empirical data on PwPs’ perceptions on their vocal problems, music and song preferences and feedback on MusVIP were documented. Implications: The findings of this study suggested that MusVIP is effective for voice rehabilitation of PwP and revealed potential benefits on QOL. This study had also gained empirical findings on the PwP’s self-perceived vocal problems, their music preferences, as well as their feedback on the studied intervention protocol. The evidence obtained from this study suggests that the MusVIP is a viable treatment option to aid voice rehabilitation of PwP.